CONSIDERATIONS ON THE EFFECTS OF TASTE CHANGES CAUSED BY LONG-COVID ON NUTRITION AND ORAL HEALTH - Sorina Mihaela Solomon; Liliana Pasarin; Irina Georgeta Sufaru; Antonela Maria Beldiman; Monica Mihaela Scutariu; Costea Claudia Florida; Georgiana Macovei (Romanian Society of Oral Rehabilitation, 2023)
Long-COVID, alternatively referred to as post-COVID syndrome, has garnered significant attention among individuals affected by SARS-CoV-2 as well as healthcare practitioners. The phenomenon began to be perceived as a secondary epidemic that is impacting an increasing number of individuals on a global scale. A notable proportion of individuals who have contracted SARS-CoV-2, including those with mild or moderate symptoms, have reported alterations in their sense of taste subsequent to the resolution of the acute stage of the disease. Patients sometimes report a frequent occurrence of an inability to interpret food tastes in a typical manner or an encounter with distorted taste perceptions. The present state of literature related to oral manifestations associated with long-term COVID-19 is still in the context of ongoing study. The nutritional imbalance observed in individuals with long-COVID syndrome may be attributed to changes in taste and smell, which affect both the quality and quantity of food intake. The changes in taste perception observed in persons suffering with long-COVID involve a complex and significant immune response that has implications for the nutritional and oral health of these patients.